Pengaruh Profitabilitas, Likuiditas, dan Aktivitas Terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Syerin Annisa Sam; Abdul Rahman Mus; Budiandriani Budiandriani (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
Abstract This study aims to determine the impact of profitability, liquidity, and activity on firm value, with capital structure as an intervening variable. The sample in this study was 28 manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the 2020-2024 period. This study used a quantitative approach with time series data. The data analysis technique used panel data regression with the help of E-Views. The results show that profitability and liquidity have a negative but significant effect on capital structure. Activity has a positive but insignificant effect on capital structure. Profitability has a positive and significant effect on firm value. Liquidity and activity have a negative but insignificant effect on firm value. Capital structure has a negative and significant effect on firm value. Capital structure is unable to mediate the effects of profitability and liquidity on firm value, while capital structure is able to mediate the effect of activities on firm value. Keywords: Profitability, Liquidity, Activities, Capital Structure, Firm Value